Analyzing Support for U.S. Presidential Candidates in Twitter Polls - Stephen Scarano; Vijayalakshmi Vasudevan; Mattia Samory; JungHwan Yang; Przemyslaw Grabowicz (Journal of Quantitative Description: Digital Media)
Polls posted on social media can provide information about public opinion on a variety of issues from business decisions to support for presidential election candidates. However, it is largely unknown whether the information provided by social polls is useful or not. To enhance our understanding of social polls, we examine nearly two thousand Twitter polls gauging support for U.S. presidential candidates during the 2016 and 2020 election campaigns.